On the coincidence of weather extremes and geopolitical conflicts: Risk analysis in regional food markets - Nkongho Ayuketang Arreyndip; Jeremy S. Pal (PLoS ONE, 2025)
Given the recent increase in geopolitical tensions between major agricultural producers and weather extremes, there is a likelihood that geopolitical conflict will occur simultaneously with weather extremes, leading to devastating production losses between the conflicting parties. These losses can affect the entire food supply chain, leading to food shortages and price increases in regional markets. This paper models the impact of these concurrent events on the global food market, using the Russian-Ukrainian war and the extreme heatwaves of summer 2022 as a case study. The model considers four war scenarios: the start of the invasion, the peak of the war, Ukraine’s resistance, sanctions against Russia, and refugee crises in Europe. Using data from the US Department of Agriculture (USDA), Statista, WITS, and Acclimate production value losses, the results show that the agricultural sectors of southern European countries such as France, Italy, and Spain were the most affected by the extreme events, although the direct impact of refugees was smaller compared to their northern counterparts. Strict sanctions against Russia coupled with Ukraine’s resistance will benefit EU food markets, but at the same time the agricultural sectors of smaller countries and weaker economies, particularly those of Russia’s allies, will be highly vulnerable. This study suggests that when developing and adopting conflict resolution strategies, their impact on weak economies should not be overlooked. An example of this policy recommendation is the continuous renewal of the Black Sea Grain Initiative to stabilize global food prices.